Penciptaan Nilai Tambah Sambal Melalui Olahan Cumi - Pura, Rahman; Sjahruddin, Herman; Hidayatullah, M. Syarif; Basir, Zulkarnain; Kanto, Muklis; Ilmi, Madinatul; Aswandi, Aswandi (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Sanrobone Village is one of the oldest villages in Takalar Regency and one of the chili producing villages, but the chilies cannot be utilized properly. When the harvest season arrives, people harvest chilies at the same time, so the price of chilies decreases, resulting in a decrease in farmers' interest in selling their chilies. People prefer to consume them privately, so rotting chilies were found on several fields. This fact underlies the implementation of Community Service (PkM) activities by increasing the usefulness of chilies through making squid chili sauce by collaborating with mothers as training participants combined with mentoring. After the training and mentoring it turned out that the village residents were very enthusiastic as evidenced by the presence of several residents who group asking for assistance (training)extra which is coupled with manufacturing practices. The positive response from residents is also in line with the market, that when marketed, Sanrobone squid chili sauce is very popular with the market, so apart from being able to increase people's knowledge, Sanrobone squid chili sauce can be used as an alternative new income.